2017
DOI: 10.1656/045.024.m1502
|View full text |Cite
|
Sign up to set email alerts
|

A Natural History of Change in Native Bees Associated with Lowbush Blueberry in Maine

Abstract: Conserving and maintaining a diverse assemblage of wild bees is essential for a healthy and functioning ecosystem, as species are uniquely evolved to deliver specific plant-pollination requirements. Understanding the biology and ecology of bees in poorly studied regions is the first step towards conservation. Detailed surveys in New Hampshire reveal a broad diversity of 118 species of wild bees in different guilds and habitats including 17 bee species representing new state records. Network analyses reveal a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 68 publications
(51 reference statements)
2
9
0
Order By: Relevance
“…In this analysis, the pollination value of wild bees was estimated based on allocating attributable net income between rented honey and wild bees based on producers' estimates of the percent fruit set from wild bees. While for wild blueberry these estimates were consistent with measured field data [61,73,74], we have no similar data for cranberry to validate producers' estimates ( Figure 4), so caution should be taken when interpreting the results for cranberry. While grower estimates of crop yield, managed bee stocking densities, and wild bee contribution to fruit is subject to bias and inaccuracies, previous work has shown that such data can be very reliable, and at times more accurate than concurrent government farm census data [75].…”
Section: Improving Valuation Metrics Of Wild Bee Pollinationsupporting
confidence: 53%
“…In this analysis, the pollination value of wild bees was estimated based on allocating attributable net income between rented honey and wild bees based on producers' estimates of the percent fruit set from wild bees. While for wild blueberry these estimates were consistent with measured field data [61,73,74], we have no similar data for cranberry to validate producers' estimates ( Figure 4), so caution should be taken when interpreting the results for cranberry. While grower estimates of crop yield, managed bee stocking densities, and wild bee contribution to fruit is subject to bias and inaccuracies, previous work has shown that such data can be very reliable, and at times more accurate than concurrent government farm census data [75].…”
Section: Improving Valuation Metrics Of Wild Bee Pollinationsupporting
confidence: 53%
“…In this analysis, the pollination value of native bees was estimated based on allocating ANI between rented honey and native bees based on producers' estimates of percent fruit set from native bees. While for wild blueberry these estimates were consistent with measured field data [63,64], cranberry in our study did not have field data that could be used to validate producers' estimates of percent fruit set from native bees (Figure 3).…”
Section: Improving Valuation Metrics Of Native Bee Pollinationsupporting
confidence: 66%
“…Air temperatures are expected to increase by 1.1-1.7 • C in the primary lowbush blueberry producing regions of North America by 2050 due to climate change [19]. Already, growers in Maine are experiencing a growing season that has increased by one month since 1950 resulting in an increase in pests and pathogens [20], fall bloom [21] and 50% more days with precipitation during bloom [22].Vaccinium angustifolium is believed to be one of the first blueberry species to be managed in North America. Clearing and burning of forests by Native Americans for harvesting occurred before the arrival of Europeans [23].…”
mentioning
confidence: 99%